DsRNA as pathogen-associated molecular pattern in innate immunity and multiple functions of the RNAi machinery complicate the use of RNAi in pest control - Feng, Min; Liu, Jisheng; Wang, Luoluo; Swevers, Luc (Frontiers in Insect Science, 2026)
In contrast to mammals, insects possess a separate machinery for processing of long dsRNAs into siRNAs for the cleavage of viral RNAs. The process of RNAi is considered very efficient in all insects once the delivery in the cytoplasm occurs such as during RNA virus replication. For the application of RNAi as insecticide to succeed, efficient uptake of intact dsRNA into the cytoplasm therefore is necessary, which seems to occur by natural mechanisms in the leaf beetles for which RNAi-based insecticides already have been marketed. In most insects, relatively high amounts of dsRNA are required to trigger gene silencing which raises questions regarding potential side effects. Besides, RNAi is considered as the major antiviral defense mechanism, at least in Drosophila, but not necessarily in all other insects. Following increasing evidence from the recent literature, it has become prudent to include the sensing of dsRNA as an immune trigger to evaluate the extent of the RNAi mechanism that is triggered by dsRNA. In this review, an overview of mechanisms is presented regarding how the recognition of dsRNA as a “pathogen-associated molecular pattern”, the multiple additional functions of the canonical siRNA factors and the modulation of the function of Dicer-2 and Ago-2 by dsRNA-binding proteins may complicate the efficiency of the exo-RNAi process and aggravate its application for pest control.